One-Pot Eco-Safe Saccharin-Catalyzed Procedure for Expedient and Convenient Synthesis of Dihydropyrano[2,3-c]pyrazole, Tetrahydrobenzo[b]pyran and Pyrano[2,3-d]pyrimidinone Scaffolds as a Green and Versatile Catalyst - Farzaneh Mohamadpour; Mojtaba Lashkari; Nourallah Hazeri (Universitas Gadjah Mada, 2018)
A green and facile saccharin-catalyzed procedure is developed for the one-pot convenient synthesis of dihydropyrano[2,3-c]pyrazole, tetrahydrobenzo[b]pyran and pyrano[2,3-d]pyrimidinone scaffolds via multi-component tandem Knoevenagel cyclocondensation reaction. This procedure has the chief advantages of green, inexpensive and readily available catalyst, high atom-economy, high to quantitative yields and the reaction procedure is mild and involves facile workup procedure to obtain the desired products in short reaction times.